This is a personal journey: a qualitative study on the influencing factors of home-based exercise rehabilitation behavior among stroke survivors - Shao, Jianing; Wang, Qing; Zhang, Xiaomin; Liu, Ke; Sha, Ling; Shi, Huiling; Cong, Sunling (Frontiers in Neurology, 2026)
BackgroundAdherence with home-based exercise rehabilitation among stroke patients is generally low. Promoting a behavioral shift from passive compliance to active participation in home-based exercise rehabilitation is crucial to address this challenge. However, there is currently a lack of in-depth exploration of the mechanisms underlying this behavioral shift among stroke patients. This study aims to explore the behaviors and influencing factors related to home-based exercise rehabilitation among stroke survivors, thereby providing a reference for the development of personalized home-based exercise rehabilitation programs.MethodsSeventeen stroke patients who visited the neurology outpatient clinic of a tertiary Grade A hospital in Nanjing, China, from October 2024 to May 2025 were recruited for semi-structured interviews. The Colaizzi seven-step analysis method was applied for thematic analysis and theme extraction.ResultsAnalysis of the interview data yielded three core themes and 12 sub-themes. These included: (1) the multidimensional influence of personal characteristics and past experiences (limited body structure and function, driven by family responsibilities, self-decision-making ability, preferences for exercise rehabilitation, and economic pressure burden); (2) the driving and constraints of behavior-related cognition (perceived effects of rehabilitation effects, rehabilitation self-efficacy, adaptability of the rehabilitation environment, and multidimensional information asymmetry); and (3) the moderating effect of behavior-related emotional responses (rehabilitation of emotional experience, family support, and peer support).ConclusionHome-based exercise rehabilitation behavior among stroke patients is influenced by multiple complex and interrelated factors. Healthcare professionals should fully consider individual differences among patients, develop tailored exercise rehabilitation programs, and strengthen diversified external support systems to improve adherence to home-based exercise rehabilitation and ultimately enhance long-term rehabilitation outcomes.